Probing the dispersive properties of optical fibers with an array of femtosecond-written fiber Bragg gratings - Tommy Boilard; Réal Vallée; Martin Bernier (Scientific Reports, 2022)
Abstract We propose an efficient method to determine the effective refractive index of step-index optical fibers from the visible to the mid-IR and thus allowing to infer their dispersive properties over a broad spectral range. The validity of the method, based on the writing of an array of fiber Bragg gratings (FBGs) with known periods using the fs scanning phase mask technique, is first confirmed with a standard silica fiber, then applied to various fluoride glass fibers to determine their effective refractive index and dispersion over more than three octaves, i.e. from 550 to 4800 nm.